New species and new records of the genus Lathrobium Gravenhorst (Coleoptera: Staphylinidae: Paederinae) from Zhejiang, East China - Zhao, Qing-Hao; Peng, Zhong (Zootaxa, 2021)
Nineteen species of Lathrobium Gravenhorst, 1802 are recorded from Zhejiang Province, East China, all of them micropterous and locally endemic. Two species are described and illustrated: L. chengi sp. n. and L. miaoi sp. n. Including the new taxa, 221 Lathrobium species are currently known from mainland China.